Cultivating progress: Greenhouse and nursery innovations for vegetable production in Guinayangan, Quezon - del Rio, Susan P.; Anunciado, Ma. Shiela S.; Oro, Emilita M.; Gonsalves, Julian F.; Laco, Jonalyn O.; Borelli, Teresa (Bioversity International and International Center for Tropical Agriculture, 2024)
The study assesses the benefits of expanding greenhouse and nursery systems including the promotion of indigenous vegetable varieties and strengthening the collaboration between farmers, local government, and other stakeholders. It also provides recommendations for improving farmers’ livelihood, enhancing food security, and promoting environmental sustainability. Through partnerships with local government units, farmer groups, and the Municipal Agriculture Office, these efforts have improved market access, supported sustainable farming practices, and encouraged community involvement. Linkages with the KADIWA program —a pioneering initiative by the Department of Agriculture, designed to strengthen the farm-to-market supply chain by directly connecting local producers with consumers and eliminating intermediary layers—have helped ensure fair pricing and market stability. The tested delivery model for selling indigenous vegetable seedlings in Guinayangan, Quezon has yielded positive results. Producing and selling these seedlings locally, has improved success rates in the raising of seedlings (under protected environments) has met market demand and created a new income stream for farmers. Moreover, it has helped in reviving public interest and the growing of a diverse range of vegetable crops previously cultivated in the locality, but that were neglected and underutilized. Small community-managed greenhouses, and seedling production systems can help improve the success rates in organic vegetable production systems. Seedling production systems can also help restore agrobiodiversity by improving accessing to planting materials of indigenous crops.